2012
DOI: 10.4161/psb.20606
|View full text |Cite
|
Sign up to set email alerts
|

Class I TCPs modulate cytokinin-induced branching and meristematic activity in tomato

Abstract: Arabidopsis TCPs are a family of basic helix loop helix (bHLH)-type transcription factors. Previous studies suggested that antagonistic activities of class I TCPs and class II TCPs are correlated with cell proliferation. We have recently shown that the class I TCPs AtTCP14 and AtTCP15 promote typical cytokinin (CK) responses in Arabidopsis, and proposed that they mediate the effect of CK on cell divisions. To further study the role of AtTCP14 and AtTCP15 in plant development, we expressed them in tomato plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
3
18
0
1
Order By: Relevance
“…Consistent with that, in tomato, increased CK levels or signaling cause the formation of ectopic meristems on the adaxial side of the leaf rachis and leaflet petiolules (Shani et al , 2010; Steiner et al , 2012). Since CK was shown to promote WUS expression in meristems (Gordon et al , 2009), the expansion of the WUS domain in meristems silenced for SlHAM s may imply that CK status increased in these meristems.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with that, in tomato, increased CK levels or signaling cause the formation of ectopic meristems on the adaxial side of the leaf rachis and leaflet petiolules (Shani et al , 2010; Steiner et al , 2012). Since CK was shown to promote WUS expression in meristems (Gordon et al , 2009), the expansion of the WUS domain in meristems silenced for SlHAM s may imply that CK status increased in these meristems.…”
Section: Discussionsupporting
confidence: 79%
“…In tomato, elevation of cytokinin (CK) levels or response enhancement led to the proliferation of ectopic shoot and inflorescence meristems on the adaxial side of the compound leaf rachis which is highly reminiscent of the phenotype observed in FIL>>MIR171b later developed leaves (Janssen et al , 1998; Kim et al , 2003; Shani et al , 2010; Steiner et al , 2012). This suggested that an increased CK level or response may be the cause of the abnormal cell proliferation observed in later developed leaf rachises of FIL>>MIR171b plants.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously suggested that class I and class II TCPs affect growth in an antagonistic manner (Li et al, 2005;Hervé et al, 2009;Koyama et al, 2010;Martín-Trillo and Cubas, 2010). Class I TCPs were recently shown to promote CK responses in both Arabidopsis and tomato (Steiner et al, 2012a(Steiner et al, , 2012b, and Arabidopsis CIN-TCP were shown to dampen CK response by activating ARR16 via an interaction with the chromatin-modifying complex BRM (Efroni et al, 2013). Moreover, BRM was recently shown to affect GA biosynthesis and response (Archacki et al, 2013).…”
Section: Ap1/ful Genes Mediate La-like Activity During Leaf Developmentmentioning
confidence: 99%
“…AtTCP15, along with its closest homolog AtTCP14, has a role in internode length and leaf shape (Kieffer et al, 2011). Both AtTCP14 and AtTCP15 are found to interact with SPINDLY (SPY) to promote cytokinin responses (Steiner et al, 2012a) and increase the sensibility to this hormone when overexpressed in tomato (Steiner et al, 2012b). …”
Section: Introductionmentioning
confidence: 99%